THE ISSUE OF PSYCHOLOGICAL AND PEDAGOGICAL TRAINING OF FUTURE SPECIALISTS IN THE CONDITIONS OF FULL-SCALE RUSSIAN AGGRESSION AGAINST UKRAINE - Vergolyas , Maya; Verholias , Olexander (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
War is always stressful for people, especially teenagers and young people, as they are the most vulnerable part of society in the process of social development and growing up. At this age, pupils and students are studying, and therefore, they are part of the circle of people who need support for their moral state. Currently, the field of psychological support in Ukraine is not sufficiently developed, so it is more difficult for Ukrainians to get out of a difficult moral situation than in other countries of Europe and America. In our time, during the war, educational institutions become the main centers of studentship, which provide not only knowledge, but also psychological support, a sense of belonging to the student community. One of the main tasks of educational institutions is daily psychological help and emotional support of participants in the educational process. First psychological aid and emotional support at all levels of educational institutions are provided by all educators. Students’ parents and mass media are also involved in the process. The use of these recommendations will help teachers to overcome psychological exhaustion during the war and will contribute to the further regulation of their psychological well-being during the training of future specialists in the conditions of the war of russian aggression against Ukraine.